SISTEM INFORMASI POTENSI INDUSTRI DI KABUPATEN BANTUL BERBASIS GEOGRAPHIC INFORMATION SYSTEM DAN LOCATION BASED SERVICE - Wibowo, Hari; Lestari, Uning; Triyono, Joko (Jurnal Script, 2014)
ABSTRACTBantul district is one of the areas that have the potential spread industry in Bantul are very diverse. But the potential of this industry has not been widely known by the public. One of the obstacles is lack of information about the location of industry. Therefore, it is necessary for Bantul regency industry website using Location Based Services (LBS) and Geographic Information System (GIS) that will assist and facilitate both the users wherever they are in order to obtain information and Bantul local government area of the promotion.(LBS) and (GIS) can be one of the main interactive tools, because the existence of (LBS) and (GIS) will described to detect the location of objects with positioning system technologies using Cell - ID which is derived from the position of Base Transceiver Station and the location of the real conditions in the industry in the form of a map. The process of making a website need to be more interesting and conveyed information quickly , accurately and efficiently.The information system of industrial potency in Bantul Regency shous wuik that reacts for position entity exchange and information about industrial level in Bantul regency such photo gallery, industrial descriptions, contact of communications in industrial side, also route and the shortest distance to industrial location.Keywords: Website, Industry, Location Based Services, Geographical Information System.